Modelagem Matemática na Educação Matemática: Uma perspectiva para a Educação de Jovens e Adultos - Domingos, Thaísa Cristina Machoski (2019)
This work presents aspects of Mathematical Modelling in Mathematics Education as one methodological alternative for High School within Education for Young People and Adults (EJA) modality. The central point of investigation is: What shows about Modelling in Mathematics Education when uses with methodology of teaching on Education for Young People and Adults? The general objective of the research is to point out the possibilities of Modeling in Mathematics Education when used as a teaching methodology in EJA - High School. From general objective, determines the specific objectives: to look at the contributions of the Mathematical Modelling as methodology to classroom, in EJA – High School modality, as of themes proposed by students, and also disseminate by means of didactic material the situations encountered by students of EJA- High School, participants of this experience. As from questions and objectives, opt to do one qualitative-interpretative search. To do the practices with modelling, was adopted Burak (1992; 2004; 2010) perspective, and to data analysis, was applied the methodological triangulation od data. The results were from analysis of practices developed by students, noting the Mathematical Modelling, in Burak (1992; 2004; 2010) perspective made a significant difference not only in mathematical content, but also to diverse scientific areas, opportunity for students to be author of their own knowledge and assisted in building of one humans more critical, reflexive and with autonomy to make decisions, beyond provide classes more dynamics and enriching, contribute to teacher being a mediator throughout its process and may rethink its pedagogical practice.